The Effect of Transformational Leadership, Work Environment, and Workload on Employee Performance at PT Pegadaian (Persero) Rantepao Branch - Vitra Vira; Adriana Madya Marampa; Astriwati Biringkanae (International Journal of Economics and Management Research, 2026)
This study aims to determine the effect of transformational leadership, work environment, and workload on employee performance at PT. Pegadaian (Persero) Rantepao branch, both partially and simultaneously. Data collection was conducted through questionnaires and documentation. The analysis method used was a quantitative approach with multiple linear regression techniques processed using SPSS version 23. The results of the simultaneous test indicate that transformational leadership, work environment, and workload together have a significant effect on employee performance. The results of the partial test (t-test) indicate that the transformational leadership variable has a t-value of 9.598, which is greater than the t-table of 2.039, thus being considered a positive and significant effect on employee performance. The work environment variable has a t-value of 2.299, which is greater than the t-table of 2.039, thus being considered a positive and significant effect. The workload variable had a t-value of 2.048, which is greater than the t-table value of 2.039, indicating a positive and significant effect. Based on these results, it can be concluded that transformational leadership, work environment, and workload have a positive and significant effect on employee performance.